Lessons Learned From 35 Cases of Laryngeal Foreign Bodies Undergoing Misdiagnosis in Pediatric Population. (February 2017) - Chen, Qingguo; Chu, Hanqi; Tao, Yanling; Huang, Hongyan; Peng, Liyan
Objectives: To present 35 cases of laryngeal foreign bodies (FBs) in pediatric population undergoing misdiagnosis so as to draw on our lessons to improve early diagnosis. Methods: A retrospective analysis over 15 years was conducted of 35 cases of laryngeal FBs undergoing misdiagnosis in children. Meanwhile, a control group, including 42 cases of laryngeal FBs without misdiagnosis in children, was set. These patients' clinical data were collected and analyzed to identify the risk factors for misdiagnosis. Results: The results of chi-square test and univariate analysis both showed a significant difference in time elapsed between discomforts and admission, witnessed foreign body (FB) aspiration history, biphasic stridor, aphonia, roentgenologic findings, and type and size of FBs between the misdiagnosed group and control group. Multivariate analysis further identified delayed doctor visits, unwitnessed FB aspiration history, nonspecific symptoms, and negative roentgenologic manifestations as independent risk factors for misdiagnosis. Conclusions: Diagnosis of laryngeal FBs, especially small, thin, and radiolucent FBs, remains a challenge. We emphasized the importance of timely doctor visits, careful clinical history inquisition, and prompt performance of radiographic or endoscopic examinations for diagnosis.